Modified Hughes Tarsoconjunctival Flap Procedure for Lower Eyelid Defect: A Case Series - Aulia; Hendriati (HM Publisher, 2025)
Background: The Hughes procedure, or tarsoconjunctival flap, is a technique used in reconstructing full-thickness lower eyelid defects involving >50% of the eyelid margin to restore anatomical integrity, function, and cosmesis of the eyelid. The modified Hughes procedure spares the marginal upper lid tarsus and removes the levator muscle aponeurosis from the tarsoconjunctival flap. This study reports a case series of patients who underwent a modified Hughes procedure after basal cell carcinoma excision. Case presentation: Two patients underwent lower eyelid reconstruction using the modified Hughes procedure. After a wide excision of the tumor, a tarsoconjunctival flap was created to reconstruct the posterior lamella of the eyelid. Subsequently, the anterior lamella of the eyelid was reconstructed using a full-thickness skin graft and an advancement flap, respectively. Both patients underwent a second surgery, tarsus flap release, 6-8 weeks after the first surgery. Postoperatively, tarsal flap apposition, skin flap/graft, and stitches were intact. After the tarsus flap release, wound healing was good. A tumor biopsy showed basal cell carcinoma. Conclusion: The modified Hughes procedure is a treatment of choice in reconstructing full-thickness lower eyelid defects involving >50% of the eyelid margin. Full-thickness skin graft and advancement flap to reconstruct the anterior lamella of the eyelid are chosen after considering skin color, texture similarity, and the laxity of the eyelid and cheek.